Correlation of distraction index with arthroscopic findings in juvenile dogs with hip dysplasia. Issue 6 (20th June 2019) - Ulfelder, Emily H.; Hudson, Caleb C.; Beale, Brian S.
Abstract: Objective: To compare distraction index (DI) with hip arthroscopy findings in juvenile dogs with hip dysplasia undergoing unilateral or bilateral double pelvic osteotomy (DPO). Study design: Retrospective case series. Animals: Twenty dogs (36 hip joints). Methods: Medical records from dogs undergoing unilateral or bilateral DPO (2011–2016) were reviewed. Distraction index was measured by using distraction view radiographs. Arthroscopic images were analyzed. Cartilage was graded by using the modified Outerbridge scale (0 = arthroscopically normal, 1 = chondromalacia, 2 = surface fibrillation, 3 = deep fissuring, 4 = full‐thickness cartilage loss, and 5 = eburnation of exposed subchondral bone). Dorsal acetabular rim, acetabular labrum, the ligament of head of the femur, and synovitis were graded by using a four‐point scale (normal, mild, moderate, severe). Spearman and Pearson correlations were used to compare DI between grade groups and age. Results: Distraction index ranged from 0.4 to 1.0 (mean 0.69 ± 0.16). Most of the hips had an arthroscopically normal femoral head and acetabulum in most regions, except for the region at the insertion of the ligament of the head of the femur. There was a low positive correlation between synovitis and DI (Spearman ρ = 0.35, P = .0346). No other differences in DI were identified between grade or age groups. Conclusion: There was a low positive correlation between synovitis and DI. No other differences in DI were identified. Clinical significance: Arthroscopic evaluation of the coxofemoral joint prior to DPO can allow detection of joint pathology that might not be appreciated by using traditional radiographic screening criteria.